Generation of functional murine CD11c+ age‐associated B cells in the absence of B cell T‐bet expression. Issue 1 (5th November 2018) - Du, Samuel W.; Arkatkar, Tanvi; Jacobs, Holly M.; Rawlings, David J.; Jackson, Shaun W.
Abstract: Age‐associated B cells (ABC), a novel subset of activated B cells defined by CD11b and CD11c expression, have been linked with both protective anti‐viral responses and the pathogenesis of systemic autoimmunity. Expression of the TH 1 lineage transcription factor T‐bet has been identified as a defining feature of ABC biology, with B cell‐intrinsic expression of this transcription factor proposed to be required for ABC formation. In contrast to this model, we report that Tbx21 (encoding T‐bet)‐deficient B cells upregulate CD11b and CD11c surface expression in vitro in response to integrated TLR and cytokine signals. Moreover, B cell‐intrinsic T‐bet deletion in a murine lupus model exerted no impact of ABC generation in vivo, with Tbx21 −/− ABCs exhibiting an identical surface phenotype to wild‐type (WT) ABCs. Importantly, WT and Tbx21 −/− ABCs sorted from autoimmune mice produced equivalent amounts of IgM and IgG ex vivo following TLR stimulation, indicating that T‐bet‐deficient ABCs are likely functional in vivo. In summary, our data contradict the established literature by demonstrating that T‐bet expression is not uniformly required for ABC generation. Abstract : Integrated B cell receptor, Toll‐like receptor, co‐stimulatory and cytokine signals promote "age‐associated B cells" (ABCs) generation during autoimmunity. Surprisingly, ABCs can form without B cell T‐bet ( Tbx21 ). Functionally, both Tbx21 +/+ and Tbx21 −/− ABCs produced autoantibodies ex vivo after TLR7 stimulation, with the impact of T‐bet limited to IgG2c class‐switched recombination.